High-definition content and file sharing networks - Petrus H. Potgieter (International Telecommunications Society (ITS), 2012)
File sharing, typically involving video or audio material in which copyright may persist and using peer-to-peer (P2P) networks like BitTorrent, has been reported to make up the bulk of Internet traffic (Pouwelse et al., 2008; Kryczka et al., 2011). The free-riding problem appears in this digital gift economy but its users exhibit rational behaviour (Becker and Clement, 2006), subject to the characteristics of the particular network (Feldman et al., 2006). The high demand for the Internet as a delivery channel for entertainment (Alleman and Rappoport, 2009) underlines the importance of understanding the dynamics of this market, especially when considering possible business models for future pricing or licensing regimes (Gervais, 2004) and for the provisioning of network capacity to support future services...
Keywords: 330